The Correlation Between Extensive Reading, Critical Reading, and Self-Esteem in Students’ Reading Abilities - Syariffudin Zuhri; Khoirul Anwar; Nirwanto Maruf (Budapest International Research and Critics University, 2021)
This study examined the relathionship between extensive reading activity (ERA) and critical reading (CR), and self esteem. To do so, many classes from second grade of science class and social class in senior high school Lamongan, They were given test of extensive reading and critical reading and questionnaire of self-worth. To attain the desires of the research, this research uses the design of correlative ponder the discoveries of the study indicated that there was highest significant relationship between extensive reading and critical reading ablity, and between in-depth reading and self esteem, and the reserch was found with highest significant among critical studying capacity and self esteem. The collected data were analyzed using a statistical regression analysis using the Pearson product moment coefficient of correlation. The discussion of the result of analysis in this scientific work, this research has three conclusions, there are ERA and CR at either the 0.05 level. And between ERA and Self Esteem (SE) at either the 0.05 level or the 0.01 stage (2-tailed). And CRA and SE at either the 0.05 level or the 0.01 level (2-tailed) too. Therefore the teacher will predict what must be developed and the way to try to do it.